Dampak Perubahan Tick Size Terhadap Likuiditas Saham (Studi Empiris pada Bursa Efek Indonesia Berdasarkan Tick Size 6 Januari 2014) - Risdy Absari Indah Pratiwi; Isfenti Sadalia; Sutarman Sutarman (Bahtera Inovasi, 2019)
The objective of the research was to find out and to analyze the influence of the change in tick size on stock liquidity and the factors which influenced stock liquidity. Tick size which became the research object in this evet study was the tick size on January 6, 2014. The sources of data were secondary data from BEI and Yahoo Finance. The samples were 147 stocks before the change in tick size and 147 stocks after the change in tick size, using purposive sampling technique.The data were analyzed by using Wilcoxon signed-rank test and regression analysis with an SPSS software program. The result of the research showed that spread and depth decreased significantly after the change in tick size. Lower spread and depth had contradictory implication on stock liquidity. Based on the dimension of immediacy cost and width, lower spread indicated that stock liquidity increased, while based on the dimension of market depth, lower depth indicated that stock liquidity decreased. In order to settlethis contradiction, the researcher used depth to spread ratio. Intuitively, this ratio measured whether the decrease in depthwas bigger or smaller that the decrease in spread. The result of Wilcoxon signed-rank test indicated that depth to spread ratio increased significantly which indicated that the decrease in depth was smaller than in spread so that it was concluded that stock liquidity increased after the change in tick size. The result of F-test showed that stock price, stock return volatility, and stock trading frequency simultaneously had significant influence on spread and depth. The result of t-test also indicated that stock price, stock return volatility, and stock trading frequency partially had significant influence on spread and depth.